PREVALENCE AND PATTERN OF MALNUTRITION AMONG CHILDREN OF WOMEN FARMERS IN NORTH EASTERN NIGERIA - M.T BOLORI (Kanem Journal of Medical Sciences, 2011)
Background. According to the 98TH World Health Assembly in 1995, about a third of the world's children were undernourished and most of them were in the developing world in which Nigeria accounted for 29 per cent. Women account for 70 to 80 per cent of household food production in sub-Saharan Africa including Nigeria. Objectives: To determine the prevalence and pattern of malnutrition among under five year old children of female farmers. Method: Study design was cross-sectional descriptive type. Multistage sampling method was used in the selection of 400 women to whom questionnaires were administered. Height and weight of their under five children were measured. Results: The study revealed that 176 (44%) were underweight out of which 19.4 per cent were wasted, 32.2 per cent were stunted and 45.4 per cent were both wasted and stunted. Conclusion: Strengthening partnership between policy makers, primary health care service providers, local government authorities and non governmental organizations (NGOs) to encourage interventional strategies is still desirable to reduce the high prevalence of malnutrition